ADOPTING VISUAL ODOMETRY FOR INDOOR MOBILE ROBOT LOCALIZATION - Sharipov, Madiyar (Nazarbayev University School of Engineering and Digital Sciences, 2022)
Localization problem is one of the primary problems for robot indoor navigation. This work discusses different types of odometry and focuses on the visual one. It implements the localization system based on the RTAB-map and compares it with such a classical approach as AMCL. The paper contain the detailed explanation of robot design for localization system implementation.
Keywords: AMCL; type of access: gated access; Research Subject Categories::TECHNOLOGY; RTAB-map; Simultaneous Localization And Mapping; SLAM; Adaptive Monte Carlo Localization; LiDAR